Extent and Characteristics of a Newly Discovered Unique Bryozoan Biogenic Reef Complex - Dutka, Travis Luke; Fejer, Alex J.; Williams, Tim; Donnelly, David M.; Flynn, Adrian J. (Frontiers in Marine Science, 2022)
Using multibeam echosounding combined with underwater observation and imagery surveys, this study sought to estimate the size and describe the characteristics of newly discovered bryozoan biogenic reefs in Western Port (Victoria, AUS). The bryozoan species forming the biogenic structure are Triphyllozoon moniliferum, T. munitum (both fenestrate forms and dominant on the reef) and Celleporaria (non-fenestrate form and sub-dominant). The bryozoan biogenic reefs occupy a total area of 1.74 km2. Their distribution appears to be geomorphically and depth-controlled, which might limit their maximum possible extent. The Western Port bryozoan reefs are unique and globally significant because they: 1) occur in shallow water (typically 5-10 metres), 2) are dominated by delicate fenestrate colonies of T. moniliferum and T. munitum, 3) have two distinct morphologies (linear and patch-like), 4) form continuous rows of reef interspersed with fine sediment, and 5) the size and vertical relief (up to approximately 1.5 meters) are among the largest recorded in the world. In Western Port, these bryozoan reefs are habitat-forming and may represent sites of enhanced biodiversity, which is currently being investigated in another separate study and are likely important habitat utilized by commercially and recreationally fished species. The bryozoan biogenic reefs are a previously unrecognised feature of conservation significance in this Ramsar site. The reefs are potentially vulnerable to physical damage from recreational fishing practices, sediment smothering and scouring, algal encroachment and hydrological alteration. Recommendations for monitoring and potential management of this unique biotope are made.